Information technology to provide ‘Health care’ for all - Editor, The (Journal of Institute of Medicine Nepal, 2011)
DOI: http://dx.doi.org/10.3126/joim.v32i2.4935 Journal of Institute of Medicine, August, 2010; 32:1-1